Prediction of high-order line-shape parameters for air-broadened O2 lines using requantized classical molecular dynamics simulations and comparison with measurements. (January 2019) - Tran, D.D.; Sironneau, V.T.; Hodges, J.T.; Armante, R.; Cuesta, J.; Tran, H.
Highlights: Calculations of air-broadened O2 lines using molecular dynamics simulations. High-order line-shape parameters were retrieved from simulated spectra. The predicted parameters were used to analyze various measured O2 lines. An agreement with measured spectra better than 1% was obtained. The temperature dependences of line-shape parameters were also predicted. Abstract: Line-shape models such as the Hartmann-Tran (HT) profile have adjustable high-order parameters that are usually determined by fits to experimental spectra. As an alternative approach, we demonstrate that fitting the HT profile to theoretical spectra provides high-order line-shape parameters for O2 transitions that are consistent with experimentally determined values. To this end, normalized absorption spectra of air-broadened O2 lines were computed without adjustable parameters using requantized classical molecular dynamics simulations (rCMDS). These theoretical calculations were made at a pressure of 203 kPa and for values of the Doppler width that cover near-Doppler-limited to collisional-broadened pressure conditions. Hartmann-Tran (HT) line profiles with adjustable line-shape parameters were then simultaneously fit to the set of rCMDS-calculated spectra in a global multispectrum analysis. The retrieved high-order line-shape parameters (i.e. the speed dependence of the line broadening and the Dicke narrowing coefficient) were subsequently used as fixed HT parameters in the analysis of seven air-broadened O2 lines of the a 1 Δ g ← X 3 Σ g − ( 0, 0 ) band. The spectra were measured over a fifteen-fold range of total gas pressure at high spectral resolution and signal-to-noise ratio with a frequency-stabilized cavity ring-down spectroscopy system. We show that these predicted parameters enable all the measured lines to be fit to within 1%, which is much better than best fits of the Voigt line profile to the measured spectra. This approach opens the route for predicting high-order line-shape parameters from first-principles calculations and for their inclusion in spectroscopic databases. Furthermore, the temperature dependences of the broadening coefficient and its speed dependent component for air-broadened O2 lines were also calculated using rCMDS.